Efficacy of Sodium-Glucose Cotransporter-2 inhibitors in heart failure patients treated with dual angiotensin receptor blocker-neprilysin inhibitor: An updated meta-analysis. (October 2021) - Yamani, Naser; Shaikh, Fahd Niaz; Sarfraz, Saba; Khan, Haider Kamal; Wasim, Muhammad Fahad; Paracha, Anousheh Awais; Almas, Talal; Mookadam, Farouk; Unzek, Samuel
Abstract: Background: Recent data suggest that the prevalence of heart failure has increased to approximately 23 million people globally. With increasing advancement in pharmacotherapeutics, Sodium-Glucose Cotransporter-2 inhibitors (SGLT2i) have garnered attention among clinicians to treat Heart failure with reduced ejection fraction (HFrEF) in diabetic as well as non-diabetic patients. Methods: MEDLINE, Scopus, Embase and Cochrane CENTRAL database were searched using relevant keywords and MeSH terms. Studies were considered only if they were randomized in nature and had a sample size >1000 HF patients. Results: Our comprehensive search strategy yielded 864 articles, of which three RCTs met the inclusion criteria with a total population of 9696. Pooled analysis revealed an association between the use of SGLT2i and decreased frequency of primary outcome irrespective of background ARNI use (HR 0.73, 95% CI [0.58–0.93], p = 0.0106; HR 0.73, 95% CI [0.66–0.81], p < 0.0001). Conclusion: This meta-analysis provides substantial evidence, to safely use SGLT2i atop ARNI therapy in select HF patients to further improve outcomes. Highlights: Heart failure (HF) prevalence has increased to approximately 23 million people globally. With advancements in treatment strategies for HF patients, a novel drug class, SGLT2i has garnered attention among clinicians. This meta-analysis collects the latest trial-based evidence and confirms the association between decreased frequency of primary outcome and SGLT2i use.